Direct Method: Solusi Penguasaan Materi Bahasa Arab pada Santri Pondok Pesantren - Amalia, Novi Nur; Satrial, Ardi; Sholihah, Qurrotush; Rahmi, Syarifatu; Rianto, Dedi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2024)
The Qawaid-translation tradition is still found in several pesantren in West Sumatra. Arabic is made as something dead or inactive. The use of the direct method with daily Arabic practice can be a solution to improving students' mastery of Arabic material. This method emphasizes props and practice as the core of learning activities. This research analyzes the improvement of students' mastery of Arabic material using the direct method. Classroom Action Research is the method of choice in this research with participant type, using observation and test techniques. Data were obtained from Arabic language teachers and 12 students. The results showed increased learning outcomes for students learning Arabic using the direct method. The acquisition of the average value of complete students increased from the pre-cycle of 51.25 to 76.75 in cycle II. This data shows that using the direct method can improve the mastery of Arabic language material in pesantren. This research has implications for the choice of teacher methods in teaching Arabic actively to enhance students' ability and learning outcomes.